2018
DOI: 10.1115/1.4040449
|View full text |Cite
|
Sign up to set email alerts
|

Roll-to-Roll Mechanical Peeling for Dry Transfer of Chemical Vapor Deposition Graphene

Abstract: Scaling up graphene fabrication is a critical step for realizing industrial applications of chemical vapor deposition (CVD) graphene, such as large-area flexible displays and solar cells. In this study, a roll-to-roll (R2R) graphene transfer system using mechanical peeling is proposed. No etching of graphene growth substrate is involved; thus, the process is economical and environmentally benign. A prototype R2R graphene transfer machine was developed. Experiments were conducted to test the effects of relevant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 37 publications
0
19
0
Order By: Relevance
“…A flexible and transparent triboelectric nanogenerator (TENG) device based on the graphene/EVA/PET electrodes can achieve current density as high as 0.075 µA cm −2 . Alternatively, the separation of copper foil and graphene/polymer film can be accomplished by mechanical dry peeling . The copper/graphene/EVA/PET film is fabricated by the similar method as mentioned above.…”
Section: Graphenementioning
confidence: 99%
“…A flexible and transparent triboelectric nanogenerator (TENG) device based on the graphene/EVA/PET electrodes can achieve current density as high as 0.075 µA cm −2 . Alternatively, the separation of copper foil and graphene/polymer film can be accomplished by mechanical dry peeling . The copper/graphene/EVA/PET film is fabricated by the similar method as mentioned above.…”
Section: Graphenementioning
confidence: 99%
“…A R2R dry transfer process was recently developed by Hao et al [27] using mechanical peeling to delaminate CVD graphene from its growth substrate. In the process, a polymer-backing layer with adhesive is first laminated onto as-grown graphene, and the laminate is then peeled with two guiding rollers on a R2R machine.…”
mentioning
confidence: 99%
“…The effort to achieve R2R peeling of largescale CVD graphene has just began. [27,[32][33][34] The work done by Hao et al [27] has demonstrated the feasibility of the R2R method. However, the peeling tensions were not actively controlled, and the quality of the transferred graphene needs to be dramatically improved to be comparable to that of wet-chemical etched samples.…”
mentioning
confidence: 99%
“…Interestingly, this group used their R2R transfer method to coat antique paintings with graphene to protect them from moisture and light that results in fading and discoloration over time [70]. The role of other parameters, such as the linear film speed, guiding roller diameter at the delamination point, and separation angle was investigated [71]. It is observed that the film speed and roller diameter have a significant effect on the transferred graphene coverage, and it is concluded that, a high speed and large roller diameter are favorable for effective transfer; 98% graphene coverage was achieved by optimizing the parameters (3 m/min speed and 51 mm roller diameter in this case).…”
Section: Roll-to-roll Transfermentioning
confidence: 99%